Distribution of Aliphatic Hydrocarbon in Coastal Surface Sediments from the Red Sea of Yemen - Al-Shwafi, Nabil A. A. (Thamar University Journal of Natural & Applied Sciences, 2023)
During the field work the author has collected samples, but the identification of oil and oil by–products accomplished at the lab. .The concentration of Aliphatic from 22.8 µgg-1 at Al-Salif Station to 21.72 µgg-1 At Ghurirah station. The unresolved complex mixture (UCM) represents components resistant to weathering and bacterial breakdown. This pollution is a consequence of localized oil operation and/or heavy ship traffic. However, some aliphatic hydrocarbons were sourced by natural biogenic processes by marine algae and phytoplankton